2020
DOI: 10.3389/fmicb.2020.597972
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin E3 Ligase c-Cbl Is a Host Negative Regulator of Nef Protein of HIV-1

Abstract: Nef is an accessory protein encoded by human immunodeficiency virus type-1 (HIV-1) and plays important roles in regulating HIV-1 infection and viral replication. Interestingly, HIV-1 Nef can promote degradation of numerous host proteins to disrupt cellular antiviral immune response. However, how HIV-1 Nef is degraded by host factors remains largely unexplored. Here, we identified c-Cbl as a host ubiquitin E3 ligase of HIV-1 Nef. We found that c-Cbl interacts with Nef and reduces protein levels of HIV-1 Nef. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, for the smooth transitioning of the HIV-1 life cycle from early to late viral gene expression, the stage-specifically expressed proteins should be degraded in a stage-specific and coordinated manner. In fact, viral proteins in HIV-1-infected cells exploit cellular machinery to decay viral and cellular proteins at every step of the HIV-1 life cycle: Nef/Env/Vpu degrade CD4 critical for the virus entry and superinfection ( Aiken et al., 1994 ; Garcia and Miller, 1992 ; Lama et al., 1999 ; Levesque et al., 2004 ; Mariani and Skowronski, 1993 ; Ruiz et al., 2010 ; Wildum et al., 2006 ; Willey et al., 1992 ), The tripartite motif-containing protein 5α (TRIM5α)-mediated degradation of Gag is integral to species tropism ( Arriagada et al., 2011 ; Battivelli et al., 2010 ; Chatterji et al., 2006 ; Sakuma et al., 2007 ; Shi and Aiken, 2006 ; Zhang et al., 2008 ), Vif/APOBEC3G determines the susceptibility of HIV-1 ( Desimmie et al., 2014 ; Ehrlich and Yu, 2006 ; Mangeat et al., 2003 ; Mariani et al., 2003 ; Stopak et al., 2003 ; Yu et al., 2003 ), c-Cbl interacts with Nef and decays it ( Zhang et al., 2020 ), and Vpu-triggered degradation of Tetherin is essential for release of the assembled virus particles ( Harris et al., 2012 ; McNatt et al., 2009 ; Miyagi et al., 2009 ; Neil et al., 2008 ), etc. Further, it is reported that HIV-1 Nef plays an important role in regulating the stability of another key HIV-1 regulatory protein, Tat ( Sugiyama et al., 2011 ).…”
Section: Ube3a In Viral Diseasesmentioning
confidence: 99%
“…Therefore, for the smooth transitioning of the HIV-1 life cycle from early to late viral gene expression, the stage-specifically expressed proteins should be degraded in a stage-specific and coordinated manner. In fact, viral proteins in HIV-1-infected cells exploit cellular machinery to decay viral and cellular proteins at every step of the HIV-1 life cycle: Nef/Env/Vpu degrade CD4 critical for the virus entry and superinfection ( Aiken et al., 1994 ; Garcia and Miller, 1992 ; Lama et al., 1999 ; Levesque et al., 2004 ; Mariani and Skowronski, 1993 ; Ruiz et al., 2010 ; Wildum et al., 2006 ; Willey et al., 1992 ), The tripartite motif-containing protein 5α (TRIM5α)-mediated degradation of Gag is integral to species tropism ( Arriagada et al., 2011 ; Battivelli et al., 2010 ; Chatterji et al., 2006 ; Sakuma et al., 2007 ; Shi and Aiken, 2006 ; Zhang et al., 2008 ), Vif/APOBEC3G determines the susceptibility of HIV-1 ( Desimmie et al., 2014 ; Ehrlich and Yu, 2006 ; Mangeat et al., 2003 ; Mariani et al., 2003 ; Stopak et al., 2003 ; Yu et al., 2003 ), c-Cbl interacts with Nef and decays it ( Zhang et al., 2020 ), and Vpu-triggered degradation of Tetherin is essential for release of the assembled virus particles ( Harris et al., 2012 ; McNatt et al., 2009 ; Miyagi et al., 2009 ; Neil et al., 2008 ), etc. Further, it is reported that HIV-1 Nef plays an important role in regulating the stability of another key HIV-1 regulatory protein, Tat ( Sugiyama et al., 2011 ).…”
Section: Ube3a In Viral Diseasesmentioning
confidence: 99%
“…and immunoprecipitation. Immunoblotting and coimmunoprecipitation were performed as previously described (11,22). The antibodies used were anti-mTOR (sc-517464; Santa Cruz Biotechnology), anti-phosphorylated S6 ribosomal protein (sc-293144; Santa Cruz Biotechnology), anti-S6 ribosomal protein (sc-74459; Santa Cruz Biotechnology), anti-Notch-1 (sc-373891; Santa Cruz Biotechnology), antiphosphorylated Akt (Ser 473 ) (9271; Cell Signaling Technology), anti-Akt (9272; Cell Signaling Technology), and anti-lysosome-associated membrane protein 1 (sc-20011; Santa Cruz Biotechnology).…”
Section: Immunoblottingmentioning
confidence: 99%
“…The function of HIV-1 Nef is multifarious, as the protein plays a critical role in: T cell activation for virus replication ( Sleckman et al., 1992 ; Salghetti et al., 1995 ; Brown et al., 1999 ; Kim et al., 1999 ; Schibeci et al., 2000 ; Wang et al., 2000 ); membrane trafficking of molecules, such as CD4 ( Guy et al., 1987 ; Garcia and Miller, 1991 ; Anderson et al., 1993 ; Mariani and Skowronski, 1993 ; Rhee and Marsh, 1994 ), major histocompatibility complex class (MHC I) ( Schwartz et al., 1996 ; Le Gall et al., 1997 ), and others ( Aiken et al., 1994 ; Schwartz et al., 1996 ) to facilitate HIV-1 infectivity and immune escape; stability of viral and cellular proteins via the ubiquitin proteasome system ( Sugiyama et al., 2011 ; Kmiec et al., 2018 ; Pyeon et al., 2019 ; Ali et al., 2020 ; Qiu et al., 2020 ; Zhang et al., 2020 ); chemotaxis ( Swingler et al., 1999 ; Choe et al., 2002 ; Park and He, 2009 ; Stolp et al., 2009 ; Stolp et al., 2012 ; Park and He, 2013 ; Rossi et al., 2016 ; Lamas-Murua et al., 2018 ); and intercellular communications through exosomes ( Lenassi et al., 2010 ; Narayanan et al., 2013 ; McNamara et al., 2018 ; Mukhamedova et al., 2019 ; Chen et al., 2020 ; Dubrovsky et al., 2020 ) and conduits/filopodia ( Xu et al., 2009 ; Nobile et al., 2010 ; Tan et al., 2013 ; Park et al., 2014 ). Molecular processes, such as signaling cascades, gene expression, etc., leading to these biological changes by HIV-1 Nef have been comprehensively investigated, as reviewed ( Renkema and Saksela, 2000 ; Abraham and Fackler, 2012 ; Felli et al., 2017 ; Heusinger and Kirchhoff, 2017 ; Buffalo et al., 2019 ; Staudt et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of all the lysine residues in Nef with arginine abolished Nef ubiquitination and subsequently CD4 downregulation ( Jin et al., 2008 ), indicating that Nef ubiquitination is important for modulating the surface expression of CD4. Degradation of Nef is mediated by interaction with c-Cbl, a host ubiquitin (Ub) E3 ligase ( Zhang et al., 2020 ), while our previous reports show that UBE3A (E6-AP), another host Ub E3 ligase, determines stability of Nef ( Pyeon et al., 2019 ). Nef can also promote proteasomal degradation of host cellular proteins, such as p53 tumor suppressor using UBE3A ( Ali et al., 2020 ) and CXCR4 by recruiting the HECT domain E3 ligases, AIP4 or NEDD ( Chandrasekaran et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%